2012
DOI: 10.1134/s0362119712010124
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the sensorimotor cortex using a device for mechanical stimulation of the plantar support zones

Abstract: Numerous studies on the mechanisms of the motor control carried out in the interests of space medicine resulted in a concept on the leading role of the support afferent input in the regulation of the pos tural tonic system in mammals. The implementation of functional magnetic resonance imaging (fMRI) has permitted in vivo brain mapping during stimulation of the support afferent input. The goal of this study was to identify activated regions in the brain during mechanical stimulation of the plantar support zone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Both organized and chaotic plantar stimulation using the Korvit system activated SM1 and S2 bilaterally. The Korvit boots were designed to stimulate the supporting areas of the feet, which have a maximal density of mechanoreceptors, in order produce gait-like somatosensory inflow ( Kremneva et al, 2012 ). Activation of SM1 was principally in the paracentral lobule, particularly on the medial surface, which relates to the lower limbs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both organized and chaotic plantar stimulation using the Korvit system activated SM1 and S2 bilaterally. The Korvit boots were designed to stimulate the supporting areas of the feet, which have a maximal density of mechanoreceptors, in order produce gait-like somatosensory inflow ( Kremneva et al, 2012 ). Activation of SM1 was principally in the paracentral lobule, particularly on the medial surface, which relates to the lower limbs.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of these areas was also found in previous reports using various plantar stimulators (vibrotactile, pneumatic etc.) ( Golaszewski et al, 2006 ; Kremneva et al, 2012 ; Hao et al, 2013 ). Moreover, the ORGANIZED > IMAGINATION contrast revealed activity in SM1 and S2 and, interestingly, was similar to the results of the motor study by Gerardin et al ( Gerardin et al, 2000 ), which demonstrated greater activation of both these regions during movement execution compared to mental imagery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical version of this suit is used for the comprehensive and drug-free treatment of cerebral palsy in children in Russia [25]. Another clinical variation of this suit is used on patients who have suffered from stroke or brain trauma [26]. 2 …”
Section: Ii7 Improving Balance and Movementmentioning
confidence: 99%